Evaluation of nutrient extraction and uptake by forage grasses under high Andean mountain conditions in Peru - Arias Arredondo, Alberto (2026)
This study evaluated nutrient extraction and uptake in native forage grasses (Festuca dolichophylla and Calamagrostis chrysantha) and improved species (Lolium perenne and Dactylis glomerata) at 4,100 m a.s.l. in the Peruvian Andes using a completely randomized design. Results revealed significant interspecific variability in nutrient accumulation. Dactylis glomerata showed superior macronutrient accumulation, particularly Mg, while Lolium perenne achieved highest K extraction (0.07 t ha⁻¹) and biomass production. Native species demonstrated lower nutritional demands: Festuca dolichophylla reached maximum dry matter production (6 t ha⁻¹), while Calamagrostis chrysantha showed elevated Ca and P concentrations. Correlation analysis revealed strong positive associations among Ca, Mg, Cu, Fe, Mn, and Zn (r = 0.7-1.0), indicating coordinated uptake mechanisms. Nickel exhibited negative correlations with P (r = -0.6) and K (r = -0.5). Improved species require intensive fertilization, while native species offer sustainable alternatives for low-input high-altitude systems.